2010
DOI: 10.1245/s10434-010-1191-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum Midkine Correlates with Tumor Progression and Imatinib Response in Gastrointestinal Stromal Tumors

Abstract: S-MK concentration is a potential marker for evaluating the progression and prognosis of GIST, especially during imatinib therapy. Further studies could focus on the role of midkine in the tumorigenesis of GIST and responsiveness toward imatinib therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…MK is described as a potential prognostic marker in several malignancies (10,(28)(29)(30)(31)(32). The present study confirmed the frequent overexpression of MK in patient-derived PDAC tissue samples.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…MK is described as a potential prognostic marker in several malignancies (10,(28)(29)(30)(31)(32). The present study confirmed the frequent overexpression of MK in patient-derived PDAC tissue samples.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our results explained for the first time how MK may trigger cancer cells to become more resistant against cell death and how it promotes cell viability (9). Recently, we and others have shown that the secretion of MK in tumor cells may serve as biomarker for gastrointestinal tumors and glioblastomas (10,11). Therefore, the development of MK inhibitors has been considered as an attractive idea to prevent tumor growth and antiapoptosis in cancer cells (12,13).…”
Section: Introductionmentioning
confidence: 56%
“…Subjects with MK levels between 650 and 1000 pg·mL −1 would be considered for active surveillance, with re-testing in 3-6 months to determine if MK levels were increasing. Fiegel et al, 2008;Ikematsu et al, 2008;Lucas et al, 2009 Glioblastoma ✓ ✓ Mishima et al, 1997;Stylianou et al, 2009 Meninginoma ✓ ✓ Tong et al, 2007 Neurofibromatosis type 1 ✓ ✓ ✓ Mashour et al, 1999; Gastric ✓ ✓ ✓ ✓ Rha et al, 1997;Ikematsu et al, 2003;Obata et al, 2005;Zhao et al, 2012 GI stromal ✓ ✓ Kaifi et al, 2007;Rawnaq et al, 2011 Bladder Brien et al, 1996;Ikematsu et al, 2003;Fiala et al, 2006;Konety, 2006 (Jia et al, 2007;Zhu et al, 2013), and the oesophageal squamous cell carcinoma markers CEA and cytokeratin 19 fragment (CYFRA21-1) (Shimada et al, 2003). However, despite the apparent superiority of MK over these established circulating biomarkers, it is extremely difficult to displace these markers in standard clinical practice.…”
Section: Mk Overexpression In Diseasementioning
confidence: 99%
“…In our another study, we combined a well known microtubule inhibitor drug vinorelbine with antiphysciotic drug lithium chloride and antidepressant drug clomipramine for neuroblastoma treatment in vitro and showed their novel mechanism of action as MDK inhibitor (Bilir et al, 2010). Rawnaq and coworkers showed that IM, a well known tyrosine kinase inhibitor,decreases MDK levels in the serums of patients with GIST (Rawnaq et al, 2010). In concomitant with these result we showed that IM also decreased MDK levels in human GBM cell lines T98G (Erguven et al, 2011).…”
Section: Midkine Inhibitorsmentioning
confidence: 60%